PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU DI SDN 548 RANTE ALANG - Darnalia; Besse Herlina; Darmawan; Hartadinata Akib; Hasni; Erni Hasmuddin; Dewi Yulianti; Nurcaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to determine the effect of the principal’s transformational leadership on teachers’ performance at SDN 548 Rante Alang. The research employed a quantitative approach with an ex post facto design, using a saturated sampling technique in which all teachers were selected as respondents. The research instrument consisted of a Likert-scale questionnaire developed based on the dimensions of transformational leadership proposed by Bernard M. Bass and teacher performance indicators aligned with the standards set by the Kementerian Pendidikan dan Kebudayaan Republik Indonesia. Data were analyzed using descriptive statistics and simple linear regression. The results indicate that both the principal’s transformational leadership and teachers’ performance are in the high category. Regression analysis shows a positive and significant effect of transformational leadership on teachers’ performance (sig < 0.05). The better the implementation of transformational leadership, the higher the teachers’ performance.